Evaluation of numerical simulation of the process of adapting internal dumping mode to the existing mining fields of the Kemerovo region - Alexey Vladimirovich Selyukov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is due to the development of technical equipment and the scale of open coal mining in the Kemerovo region under condition of agricultural land limitation. Through the use of a special method of mining-geometric analysis of mining field (defining the stages and phases of mining) and technological design of mining systems, technologies of mining queues were developed when you change the direction of heading of mining work. In the first step of this phase of mining is the movement of the bench operations across the strike of the strata to a certain intermediate depth of development primarily with external dumping of overburden, and at the second stage of mining is the movement along the strike of the strata to the final depth of development with predominantly internal dumping. These technologies are called flexible due to a dynamic approach to determining the border between stages and queues for each specific field. The main aim of the study is modernization of spatial planning decisions on the organization of the technological process for internal dumping of overburden on existing mining fields. The methods used in the study: combined analysis of design and actual data on the current state of internal dumping in the development of inclined and steeply dipping deposits in the Kemerovo region, special methods of mining-geometric analysis of mining fields in the context of structurally-parametric studies and techno-economic analysis of the proposed solutions using Excel spreadsheet. Results. The authors proposed rational parameters of internal dumps formation in the conversion process of longitudinal cross system open development into cross development system thereby providing more efficient retrieval to technological and environmental advantages of internal dumping at all the stages due to the additional dumping of one or another intermediate contour of the overburden rocks.